The genus Harpactea Bristowe, 1939 (Araneae, Dysderidae) from the Jijel region (Algeria), with the description of a new species - Kahlessenane, Soufyane; Bouseksou, Samira; Kherbouche-Abrous, Ourida; Moulaï, Riadh; Bosmans, Robert; Beladjal, Lynda (Zootaxa, 2025)
Harpactea jijelensis sp. nov. (♂♀) is described from Jijel, north-east Algeria. The new species is assigned to the corticalis species group and the auriga subgroup, based on the distinctive characteristics of the male. A detailed description, along with diagnostic characters, and illustrations of the genitalia for both sexes are provided. Additionally, information on the species’ abundance, and distribution across various habitats in the region is presented. New distribution records for Harpactea acuta Beladjal & Bosmans 1997 and Harpactea innupta Beladjal & Bosmans 1997 are presented.